Loss of Polyoma Virus Infectivity as a Result of a Single Amino Acid Change in a Region of Polyoma Virus Large T-Antigen Which Has Extensive Amino Acid Homology with Simian Virus 40 Large T-Antigen - Hayday, Adrian C. (1983)
The polyoma virus (Py) transformed cell line 7axB, selected by in vivo passage of an in vitro transformed cell, contains an integrated tandem array of 2.4 genomes and produces the large, middle, and small Py T-antigen species, with molecular weights of 100,000, 55,000, and 22,000, respectively (Hayday et al., J. Virol. 44:67-77, 1982; Lania et al., Cold Spring Harbor Symp. Quant. Biol. 44:597-603, 1980). The integrated viral and adjacent host DNA sequences have been molecularly cloned as three EcoRI fragments (Hayday et al.). One of these fragments (7B-M), derived from within the tandem viral sequences, is equivalent to an EcoRI viral linear molecule. Fragment 7B-M has been found to be transformation competent but incapable of producing infectious virus after DNA transfection (Hayday et al.). By constructing chimerae between 7B-M and Py DNA and by direct DNA sequencing, the mutation responsible for the loss of infectivity has been located to a single base change (adenine to guanine) at nucleotide 2503. This results in a conversion of an aspartic acid to a glycine in the C-terminal region of the Py large T-antigen but does not appear to affect the binding of the Py large T-antigen to Py DNA at the putative DNA replication and autoregulation binding sites. The mutation is located within a 21-amino acid homology region shared by the simian virus 40 large T-antigen (Friedmann et al., Cell 17:715-724, 1979). These results suggest that the mutation in the 7axB large T-antigen may be involved in the active site of the protein for DNA replication.